Business communication essentials - Bovâee, Courtland L
Understanding business communication in today's workplace -- Mastering team skills and interpersonal communication -- Planning business messages -- Writing business messages -- Completing business messages -- Crafting messages for electronic media -- Writing routine and positive messages -- Writing negative messages -- Writing persuasive messages -- Understanding and planning reports and proposals -- Writing and completing reports and proposals -- Developing oral and online presentations -- Building careers and writing râesumâes -- Applying and interviewing for employment.; Previous edition: 2012; Includes bibliographical references and index